2012
DOI: 10.1055/s-0032-1329686
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Nutrient Intake and Risk of Preterm Delivery

Abstract: Objective To examine maternal dietary intake and preterm delivery. Study Design Data included 5738 deliveries from the National Birth Defects Prevention Study. Odds ratios (ORs) reflected risks of delivery at <32, 32–34, or 35–36 versus ≥37 weeks for maternal intake in the lowest or highest quartile of nutrient intake compared with the middle two. Results Among deliveries < 32 weeks, many ORs were ≥1.5 or ≤0.7, but few confidence intervals excluded one. ORs were 1.5 for lowest quartiles of protein, thiamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The literature search identified four studies which measured dietary zinc intakes during pregnancy and sPTB with varying conclusions (Table 3) [43,44,94,95]. Two of these studies, which analyzed 5738 and 818 women respectively, determined that low zinc intake (≤6 mg/day which is ≤54% of the recommended 11 mg/day [21]) was associated with a more than 2-fold increase in the risk of delivering preterm (aOR: 2.3, 95% CI: 1.2–4.5 and aOR: 1.85 95% CI: 1.09–3.12, respectively), after adjusting for factors such as ethnicity, pre-pregnancy BMI, smoking, alcohol and multivitamin consumption [44,94].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified four studies which measured dietary zinc intakes during pregnancy and sPTB with varying conclusions (Table 3) [43,44,94,95]. Two of these studies, which analyzed 5738 and 818 women respectively, determined that low zinc intake (≤6 mg/day which is ≤54% of the recommended 11 mg/day [21]) was associated with a more than 2-fold increase in the risk of delivering preterm (aOR: 2.3, 95% CI: 1.2–4.5 and aOR: 1.85 95% CI: 1.09–3.12, respectively), after adjusting for factors such as ethnicity, pre-pregnancy BMI, smoking, alcohol and multivitamin consumption [44,94].…”
Section: Resultsmentioning
confidence: 99%
“…Two of these studies, which analyzed 5738 and 818 women respectively, determined that low zinc intake (≤6 mg/day which is ≤54% of the recommended 11 mg/day [21]) was associated with a more than 2-fold increase in the risk of delivering preterm (aOR: 2.3, 95% CI: 1.2–4.5 and aOR: 1.85 95% CI: 1.09–3.12, respectively), after adjusting for factors such as ethnicity, pre-pregnancy BMI, smoking, alcohol and multivitamin consumption [44,94]. If delivery date was calculated by last menstrual period (LMP), zinc intake below 9 mg/day was associated with a 2.75-fold increased risk in delivering <32 weeks gestation (aOR: 2.75, 95% CI: 1.31–5.77) [44].…”
Section: Resultsmentioning
confidence: 99%
“…Copper is an essential cofactor for numerous enzymes involved in various biological processes. The effect of maternal copper concentration is not well understood with some studies suggesting increased preterm birth with copper deficiency [21]- [24] and others reporting no association [25], [26]. Zinc is a crucial component of many metalloenzymes participating in protein and carbohydrate metabolism, nucleic acid synthesis and antioxidants functions through Cu/Zn superoxide dismutase [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested maternal nutrients maybe associated with low birth weight and preterm birth, such as iron and zinc [8,9]. However, maternal dietary nutrients, as the main source of nutrition for both mothers and fetuses, have been studied less in relation to their association with preterm birth [10,11], especially among Chinese pregnant women. This study aimed to investigate dietary nutrient intake among Chinese pregnant women and explore the association between dietary nutrients and preterm birth using a case-controlled study design in Beijing, China.…”
Section: Introductionmentioning
confidence: 99%